Factor Structure of the Cultural Competence Items in the National Home and Hospice Care Survey. Issue 4 (April 2018) - AbuDagga, Azza; Mara, Constance A.; Carle, Adam C.; Weech-Maldonado, Robert
Abstract : Background: There is a need for validated measures of cultural competency practices in home health and hospice care (HHHC). Objective: To establish the factor structure of the cultural competency items included in the agency-component of the 2007 public-use National Home and Hospice Care Survey file. Data Source: We used weighted survey data from 1036 HHHC agencies. Research Design and Participants: We used exploratory factor analyses to identify a preliminary factor structure, and then performed confirmatory factor analysis to provide further support for identified factor structure. Measures: We examined 9 cultural competency items. Results: Exploratory factor analyses suggested an interpretable 2-factor solution: (1) the provision of mandatory cultural competency training; and (2) the provision of cultural competency communication practices. Each factor consisted of 3 items. The remaining 3 items did not load well on these factors. A similar, but more restrictive, confirmatory factor analysis model without cross-loadings supported the 2-factor model: =9.50, P =0.30, root mean square error of approximation (RMSEA)=0.01, comparative fit index (CFI)=0.99, Tucker-Lewis Index (TLI)=0.99. Conclusions: Two constructs with 3 items each appeared to be internally valid measures of cultural competency in this nationally representative survey of HHHC agencies: cultural competency training and cultural competency communication practices. These measures could be used by HHHC managers in quality improvement efforts and by policy makers in monitoring cultural competency practices.